The French Italian [videorecording (DVD)] - Wolther, Rachel; Cohen, Catherine, 1991-; Athari, Aristotle; Cherry, Chloe (Level 33 Entertainment, 2026)
When a young New York City couple are terrorized by their noisy downstairs neighbor, who happens to be a failed actress, they decide to get revenge by casting her in a fake play in order to humiliate her. However, the couple soon get sucked into the process of producing theater and start to believe that becoming artists is their true calling.